A study of outsourcing material availability decision-making - Dr. Surender Kumar (Innovative Research Thoughts, 2022)
Strong analytical models and design tools are necessary for efficient supply chain design. Previous research in this field has mainly focused on operations research without taking manufacturing into account. Researchers have recently started to realise that the manufactured product, specifically its characteristics and life cycle, should be the driving force behind supply chain design decisions and integration efforts. “A thorough collection of performance measures should also be used to guide decision-making processes. The supply chain operations reference (SCOR) model level I performance indicators are used as the decision criterion in this study as we establish a relationship between product attributes and supply chain strategy. Then, to account for both qualitative and quantitative elements in supplier selection, an integrated analytic hierarchy process (AHP) and pre-emptive goal programming (PGP) based multi-criteria decision-making methodology is established. PGP uses mathematics to estimate the ideal order quantity from the selected suppliers, whereas the AHP approach aligns product features with supplier qualities (using supplier ratings resulting from pairwise comparisons) to decide supply chain strategy qualitatively. The variations in pairwise comparisons in AHP will affect the final order quantity because PGP employs AHP ratings as an input. To assure the accuracy of supplier evaluations, users of this methodology should therefore place more focus on the AHP development.